CASE REPORT: STRONGYLOIDES HYPERINFECTION SYNDROME IN A PATIENT WITH DRUG-INDUCED CUSHING’S SYNDROME DUE TO PROLONGED CORTICOSTEROID USE (Vietnam Journal of Community Medicine, 2026)
Background:  Strongyloidiasis is prevalent in tropical and subtropical regions. In immunocompromised individuals, infection with Strongyloides stercoralis can trigger Strongyloides hyperinfection syndrome (SHS), a severe condition that often carries a high mortality rate. We report a severe case of hyperinfection syndrome in an elderly patient with knee osteoarthritis whose prolonged use of anti-inflammatory corticosteroids led to drug-induced Cushing's syndrome and type 2 diabetes mellitus.Results:  A 74-year-old female patient from Long An province, with a history of long-term corticosteroid therapy for knee osteoarthritis, was admitted with progressive dyspnea and fatigue. Her respiratory distress worsened rapidly, requiring initial oxygen therapy via a reservoir mask, followed by endotracheal intubation and mechanical ventilation. Sputum and stool examinations revealed S. stercoralis larvae. Blood cultures were positive for Enterococcus faecium sensitive to vancomycin. Notably, the peripheral blood eosinophil count was within the normal range at the time of admission. During the clinical course, the patient developed severe pneumonia complicated by Acute Respiratory Distress Syndrome (ARDS) and upper gastrointestinal bleeding suspected to be due to peptic ulcer disease. Treatment included Ivermectin, combined with Meropenem and Vancomycin. The patient was successfully weaned from the ventilator after 9 days and was discharged in stable condition after 16 days of treatment.Case presentation:  Strongyloides hyperinfection syndrome in patients on long-term corticosteroid therapy presents a poor prognosis, often manifesting as ARDS and secondary sepsis. The absence of eosinophilia poses a significant diagnostic challenge and can lead to missed diagnoses. Proactive parasite screening prior to initiating immunosuppressive therapy, along with early administration of high-dose Ivermectin and intensive care support, are crucial to improving clinical outcomes.
Keywords: Strongyloides hyperinfection syndrome, Strongyloides stercoralis, Enterococcus faecium, Pneumonia, ARDS.